IMPLEMENTASI KONSEP EKONOMI SIRKULAR DALAM PROGRAM DAUR ULANG LIMBAH BAN BEKAS UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Riza Amalia Rifani; Siti Diva Syarifah Lukman; Mulyana Machmud; Hartati (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
This activity aims to implement the concept of circular economy in the used tire waste recycling program to improve the welfare of the community, in this case, the partners of used tire waste craftsmen in Tellumpanua village. The service team will provide an understanding of the concept of circular economy, improve practical skills in processing used tires, encourage active participation in the recycling program, and measure the impact of the program on waste reduction and economic improvement. This activity uses an educational approach, namely lectures, discussions, and demonstrations measured by direct observation methods, to measure partners' progress in practical skills and the impact of the program on the production of recycled products and waste reduction. The results of this activity showed an increase in partners' knowledge and understanding of the circular economy concept by 50% after attending lecture and discussion sessions and 100% after the demonstration. The products produced in this activity are tables, chairs, and flower vases that have a more attractive design than before. This activity has provided tangible benefits in the form of waste reduction and improved quality of waste tire recycling products.  ---  Kegiatan ini bertujuan untuk mengimplemtasikan konsep ekonomi sirkular dalam program daur ulang limbah ban bekas untuk meningkatkan kesejahteraan masyarakat dalam hal ini mitra pengrajin limbah ban bekas di desa Tellumpanua. Tim pengabdian akan memberikan pemaham tentang konsep ekonomi sirkular, meningkatkan keterampilan praktis dalam mengolah ban bekas, mendorong partisipasi aktif dalam program daur ulang, dan mengukur dampak program terhadap pengurangan limbah dan peningkatan ekonomi. Kegiatan ini menggunakan pendekatan edukasi, yakni ceramah, diskusi, dan demonstrasi yang diukur dengan metode pengamatan langsung untuk mengukur kemajuan mitra dalam keterampilan praktis dan dampak program terhadap produksi produk daur ulang dan pengurangan limbah. Hasil kegiatan ini menunjukkan adanya peningkatan pengetahuan dan pemahaman mitra mengenai konsep ekonomi sirkular sebanyak 50% setelah mengikuti sesi ceramah dan diskusi serta 100% setelah demonstrasi. Produk yang dihasilkan dalam kegiatan ini berupa meja, kursi, dan vas bunga yang memiliki desain yang lebih menarik dari sebelumnya. Kegiatan ini telah memberikan manfaat nyata berupa pengurangan limbah dan peningkatan kualitas produk daur ulang limbah ban bekas.